PENERAPAN MEDIA PEMBELAJARAN AUDIO VISUAL BERBASIS CAPCUT DALAM MENINGKATKAN KOSA KATA (MUFRADAT) PESERTA DIDIK DALAM PEMBELAJARAN BAHASA ARAB KELAS V DI SD IT AL-MADINAH MAROS - Nisar; Qahar Zainal, Abdul; Wahab, Abdul; Muhammad; Azhar, Muh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the low mastery of Arabic vocabulary (mufrodat) among students during the learning process. This condition is caused by the lack of variety in teaching methods and the suboptimal use of engaging and contextual learning media. The purpose of this research is to examine the implementation and effectiveness of audio-visual learning media using the CapCut application in improving the vocabulary mastery of Grade V students at Al-Madinah Islamic School Maros. This research is a Classroom Action Research (CAR) conducted in two cycles. Each cycle consisted of four stages: planning, implementation, observation, and reflection. The subjects of this study were 25 students. Data were collected through observation, interviews, documentation, and learning evaluation tests. The results of the study showed an improvement in student learning outcomes from the first to the second cycle. In the first cycle, the average student score was 72.8, with 18 students (72%) achieving the minimum mastery criteria. After revisions in the second cycle, the average score increased to 78.8, with 22 students (88%) achieving mastery. The reflection stage indicated that the use of CapCut media enhanced students’ motivation, engagement, and understanding of vocabulary material.